A review of antioxidant N-acetylcysteine in addressing polycystic ovary syndrome - Pu Yifu (Taylor & Francis Group, 2024)
N-acetylcysteine (NAC), a compound known for its cysteine and glutathione precursor properties, has been used in therapeutic applications for many years. Recently, there has been increasing interest in exploring the potential benefits of NAC in addressing polycystic ovary syndrome (PCOS). However, the exact mechanisms underlying NAC's therapeutic and clinical uses remain not fully understood. This review aims to specifically investigate how NAC offers protection against PCOS. This involved an extensive systematic review of the literature, and it made use of PubMed, Embase, and Web of Science databases. By analyzing key findings from over 100 research papers, the potential mechanisms through which NAC produces its effects were explored and summarized. Most studies suggest that NAC, whether used on its own or in combination with other medications, has the potential to counteract oxidative stress, utilize its anti-inflammatory and anti-apoptotic properties, and offer benefits in managing PCOS. Moreover, NAC might have the potential to influence specific signaling pathways in insulin target cells and β cells. Diverse biological effects of NAC indicate its potential usefulness as a supplementary or therapeutic approach for managing PCOS. As a result, additional research is required to explore its potential in addressing PCOS.